Top-down influences on visual processing - Gilbert, Charles D.; Li, Wu (Nature reviews. Neuroscience, 2013)
Key Points In contrast to the traditional idea that the processing of visual information consists of a sequence of feedforward operations, with neuronal functional properties taking on increasing complexity as the information progresses through a hierarchy of cortical areas, increasing evidence points towards a reverse process, with higher-order cognitive influences interacting with information coming from the retina. Thus, rather than having a fixed functional role, neurons should be thought of as adaptive processors, changing their function according to the behavioural context. Vision is an active process in which higher-order cognitive influences affect the operations performed by cortical neurons. Visual pathways operate bidirectionally, with each feedforward connection being matched by feedback or re-entrant connections going from higher- to lower-order cortical areas. Top-down influences include various forms of attention, such as spatial, object oriented and feature oriented attention. Top-down influences are not limited to attention but mediate a much broader range of functional roles, including perceptual task, object expectation, scene segmentation, efference copy, working memory and the encoding and recall of learned information. The effect of top-down influences is to change the information conveyed by neurons, both by altering the tuning of their responses to stimulus attributes and by changing the structure of correlations over neuronal ensembles. All areas of the visual pathway, except for the retina, are subject to top-down influences, including early cortical stages of visual processing such as the primary visual cortex and the lateral geniculate nucleus, and all areas along the dorsal and ventral visual cortical pathways. Each area contains an association field of potential interactions, and expresses a subset of these interactions to execute different functions. The sources of top-down influences are widespread, with each area providing information reflecting the functional properties of that area. As a consequence, even a single neuron can be viewed as a microcosm of activity occurring throughout the visual pathway. We propose that the circuit mechanism of top-down control and adaptive processing involves a gating of intrinsic cortical circuits within an area mediated by long-range feedback connections to that area. By selecting a subset of inputs, a neuron can express different components of its association field, and as a result take on different functional roles. Vision is an active process. Higher-order cognitive influences, including attention, expectation and perceptual task, as well as motor signals, are fed into the sensory apparatus. This enables neurons to dynamically tune their receptive field properties to carry information that is relevant for executing the current behavioural tasks. Re-entrant or feedback pathways between cortical areas carry rich and varied information about behavioural context, including attention, expectation, perceptual tasks, working memory and motor commands. Neurons receiving such inputs effectively function as adaptive processors that are able to assume different functional states according to the task being executed. Recent data suggest that the selection of particular inputs, representing different components of an association field, enable neurons to take on different functional roles. In this Review, we discuss the various top-down influences exerted on the visual cortical pathways and highlight the dynamic nature of the receptive field, which allows neurons to carry information that is relevant to the current perceptual demands.